New Insights in CaVβ Subunits: Role in the Regulation of Gene Expression and Cellular Homeostasis - Vergnol, Amélie; Traoré, Massiré; Pietri-Rouxel, France; Falcone, Sestina (Frontiers in Cell and Developmental Biology, 2022)
The voltage-gated calcium channels (CaVs or VGCCs) are fundamental regulators of intracellular calcium homeostasis. When electrical activity induces their activation, the influx of calcium that they mediate or their interaction with intracellular players leads to changes in intracellular Ca2+ levels which regulate many processes such as contraction, secretion and gene expression, depending on the cell type. The essential component of the pore channel is the CaVα1 subunit. However, the fine-tuning of Ca2+-dependent signals is guaranteed by the modulatory role of the auxiliary subunits β, α2δ, and γ of the CaVs. In particular, four different CaVβ proteins (CaVβ1, CaVβ2, CaVβ3, and CaVβ4) are encoded by four different genes in mammalians, each of them displaying several splice variants. Some of these isoforms have been described in regulating CaVα1 docking and stability at the membrane and controlling the channel complex’s conformational changes. In addition, emerging evidences have highlighted other properties of the CaVβ subunits, independently of α1 and non-correlated to its channel or voltage sensing functions. This review summarizes the recent findings reporting novel roles of the auxiliary CaVβ subunits and in particular their direct or indirect implication in regulating gene expression in different cellular contexts.